Development and characterisation of Mycelium bio-composites produced from Pleurotus ostreatus by using paddy straw and cotton wastes - Ghani, N. A.A.; Umor, N. A.; Huzaifah, M. R.M.; Yahya, M. H.M. (Akademi Sains Malaysia, 2025)
Mycelium biocomposites are a combination of mycelium and agricultural waste or organic matter from industrial waste. Agricultural productivity has increased due to the growing need to feed the world’s population. The lack of studies on the treatment of this waste can lead to significant financial losses and pose a significant risk to human health due to environmental pollution, as most of it has been burnt in open areas. Fungi can solve this problem by utilising agricultural waste as a source of sustainable building materials through the growth of mycelium. Therefore, the study focussed on the local production of mycelium. The surface area, weight, moisture, density, morphological analysis and compressive strength were measured to determine the physico-chemical and mechanical properties of mycelium in different substrates. 100 g of rice straw and cotton soaked in hydrated lime were mixed with 3 g of Pleurotus ostreatus mushrooms in a transparent plastic bag, and the mycelium grew for about two months. The results show that paddy straws have a larger surface area (179.33cm2) than cotton (129.67cm2), which is due to the different surface dimensions (size, shape and weight). However, the compression resistance at 20% deformation test shows that cotton has a higher result, 0.09130 MPa and 0.01619 MPa for rice straw. This study shows that the development of mycelium in cotton and rice straw shows positive results. Their mechanical and physical properties also vary depending on how well they absorb water and how different their densities are. It is advisable to conduct further research in the future to determine which substrate is most suitable for a particular type of mushroom to be used and to standardise size, shape and weight to obtain reliable results.